Pengaruh Stres Kerja Dan Desain Pekerjaan Terhadap Kinerja Karyawan di Front Office Department Sheraton Grand Jakarta Gandaria City Hotel - Siboro, Pretty Shinta; Wulandari, Dwi Pratiwi (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
Examining how job design and stress affect front desk performance at the Sheraton Grand Jakarta Gandaria City Hotel is the primary goal of this research. This study is grounded in the problem of diminishing staff performance quality in this department, which includes things like making mistakes during check-in, not paying attention to guest complaints, and having too much work to do. The ideal performance of hotel employees is shaped by a combination of job design and the impact of work stress, which are the two primary variables investigated in this study. Using a causal associative approach, this study employs a quantitative methodology. Thirty permanent employees served as the sample for this investigation, which utilized the complete sampling technique. Questionnaires with a Likert scale will be distributed in order to gather the necessary data, which will then be analyzed using SPSS. Multiple linear regression, coefficients of determination, reliability tests, validity tests, and classical assumption tests are some of the analytical procedures utilized. According to this study's findings, job design positively impacts employee performance, whereas employment stress negatively impacts performance. At the same time, both factors significantly impact employee performance in the front desk department of the Sheraton Grand Jakarta Gandaria City Hotel. This suggests that job design and levels of work stress account for nearly half of the variation in performance. The significance of stress management and well-designed jobs in enhancing hospitality workers' performance has been borne out by this discovery